2010
DOI: 10.1074/jbc.m110.144279
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like Protein 3 Inhibits Lipoprotein Lipase Activity through Enhancing Its Cleavage by Proprotein Convertases

Abstract: Lipoprotein lipase (LPL)-mediated lipolysis of triglycerides is the first and rate-limiting step in chylomicron/very low density lipoprotein clearance at the luminal surface of the capillaries. Angiopoietin-like protein 3 (ANGPTL3) is shown to inhibit LPL activity and plays important roles in modulating lipoprotein metabolism in vivo. However, the mechanism by which it inhibits LPL activity remains poorly understood. Using cell-based analysis of the interaction between ANGPTL3, furin, proprotein convertase sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 31 publications
5
80
1
Order By: Relevance
“…ANGPTL4 and ANGPTL3 are similar in that both have the ability to enhance LPL cleavage by PCs and that this property is not influenced by the extent to which they themselves are cleaved (26) (Fig. 5).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…ANGPTL4 and ANGPTL3 are similar in that both have the ability to enhance LPL cleavage by PCs and that this property is not influenced by the extent to which they themselves are cleaved (26) (Fig. 5).…”
Section: Discussionmentioning
confidence: 85%
“…5). This effect also seems LPL-specific (26). ANGPTL3 cleavage is reported to be affected by the O-glycosylation state of threonine at amino acid position 226 by polypeptide N-acetylgalactosaminyltransferase 2, adjacent to the proprotein convertase-processing site (27).…”
Section: Discussionmentioning
confidence: 99%
“…Since LPL mediates the hydrolysis of triglycerides (TG), the proteolytic processing of ANGPTL4 by PCs including furin can markedly increase plasma TG levels. Moreover, Liu et al [18] observed that ANGPTL3, besides ANGPTL4, can also amplify the cleavage of LPL by enhancing the activity of endogenous furin and PACE4, but not by PCSK5, and this effect is LPL-specific. Furthermore, this process also results in the inactivation of LPL and the dissociation of LPL from the cell surface, a process that raises plasma TG levels.…”
Section: Etiologicalmentioning
confidence: 99%
“…Interestingly, however, they found that GPIHBP1-bound LPL was not susceptible to inhibition by ANGPTL3 and ANGPTL4. In a subsequent study, Liu et al ( 59 ) reported that ANGPTL3 inactivates LPL by increasing its susceptibility to endoproteolytic cleavage by proprotein convertases ( 59 ). In their hands, soluble GPIHBP1 did not protect LPL from this cleavage event.…”
Section: Identifi Cation Of a Role For Gpihbp1 In Lipolysismentioning
confidence: 99%